Evaluasi Kesuksesan Sistem Informasi Akademik (SIAMIK) dengan Model DeLone dan McLean - Alfredo Gormantara; Elisabeth Elisabeth (Universitas Negeri Padang, 2022)
Evaluation of information systems is needed to determine the quality of system use. Therefore, it is necessary to measure the success of an information system, one of which is the DeLone and McLean model, which consists of six factors measuring the success of an information system. SIAMIK is an academic information system designed to meet the minimum requirements needed in processing academic information. This research is divided into several stages to test the 10 initial hypotheses. The data collected were 1560 correspondents from questionnaires distributed to students as SIAMIK users. Furthermore, the results of the validity and reliability tests were continued with SEM analysis for hypothesis testing. The evaluation results were obtained for the 10 hypotheses that have been formed. there are 3 accepted hypotheses and 7 rejected hypotheses. Therefore, it can be concluded that the use of SIAMIK within the scope of Atma Jaya Makassar University has not been successful.